Transformasi Pendidikan Anak Usia Dini dan Sekolah Dasar melalui Gamifikasi Digital: Solusi Kreatif untuk Meningkatkan Keterlibatan dan Prestasi Belajar - Ocha, Fifi Arisanti; Dwi Laksana, Sigit (Journal of Early Childhood Education Studies, 2025)
This study aimed to explore the transformation of early childhood and primary education through the integration of digital gamification as a creative approach to enhancing student engagement and academic achievement. The research employed a qualitative descriptive method with data collected through classroom observations, interviews with teachers and parents, and document analysis in selected early childhood education centers and primary schools in Ponorogo. The study focused on identifying the impact of digital gamification tools such as educational apps, interactive games, and reward-based learning systems on learning motivation, active participation, and performance outcomes. Results showed that students who engaged with gamified digital learning activities demonstrated higher levels of enthusiasm, longer attention spans, improved concept understanding, and better learning retention. Teachers reported that digital gamification fostered more interactive and student-centered classrooms, while parents acknowledged increased motivation and enjoyment in learning at home. The study also revealed that the successful implementation of digital gamification depended heavily on the role of educators and parents as facilitators, as well as access to technology and digital literacy. The integration of gamification was found to align with indicators of early childhood development and primary education learning outcomes, especially in stimulating creativity, collaboration, and cognitive development. This research contributes to the growing body of knowledge supporting innovative pedagogical practices in the digital era and recommends further development of culturally adaptive gamification tools tailored to the local educational context. It highlights the urgency of embracing digital transformation in education to meet the evolving needs of 21st-century learners.